Distribution of Contaminant Trace Metals Inadvertently Provided by Phosphorus Fertilisers: Movement, Chemical Fractions and Mass Balances in Contrasting Acidic Soils - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Springer Netherlands, 2018)
The frequent use of phosphorus (P) fertilisers accompanied by nitrogen and potassium sources may lead to a serious long-term environmental issue because of the presence of potentially hazardous trace metals (TM) in P fertilisers and unknown effects on the TM chemical fractions in agricultural soils. A 16-month-long column experiment was conducted to investigate the mobility and chemical forms of Cd, Cu, Cr, Ni, and Zn introduced into a Mollisol and an Andisol through surface incorporation (0–2 cm) of triple superphosphate (TSP) fertiliser. The effects of urea and potassium chloride (KCl) applications were investigated as well. After 15 cycles of 300-mm irrigation, TSP addition increased the 4 M HNO 3 extractable TM concentration in the upper (0–5 cm) section of soils. Beyond this depth, metals showed no significant mobility, with minimal leaching losses (< 1.9%, 25-cm depth). The TM chemical forms in the 0–5 cm section were significantly (p < 0.01) affected by the soil type and fertilisers addition. Cadmium, Ni, and Zn were the elements which appeared in a larger proportion (up to 30%) in the most labile fraction (KNO 3 extractable) in fertilised soils. The impact of urea depended on the nitrification-related changes in soil pH, while fertilisation with KCl tended to increase the KNO 3 fraction of most metals probably due to K + exchange reactions. Chromium remained minimally affected by the urea and KCl applications since this contaminant is strongly bound to the less labile solid phases. The low mobility of TM was governed mainly by their interaction with the solid phases rather than by their speciation at soil pH. The mass balance showed that the geochemical processes underwent in time by the P fertiliser increased the amount of TM extracted by the chemical fractionation scheme, therefore the reaction period of TSP with soil particles should be taken into account for evaluating TM availability. Long-term soil fertilisation could inadvertently contribute to an increased concentration and availability of these P fertilisers-born contaminants in the cultivated layer of acidic soils. © 2018, Springer Science+Business Media B.V., part of Springer Nature.
Keywords: Sequential extraction; Heavy metals; Triple superphosphate; Soil contamination